Hypertrophic lichen sclerosus sine sclerosis: clues to histopathologic diagnosis when presenting as psoriasiform lichenoid dermatitis. (23rd December 2014) - Weyers, Wolfgang
<x xml:space="preserve">Abstract</x> Background The histopathologic diagnosis of lichen sclerosus (LS) is usually facilitated by a subepidermal zone of sclerosis. In the absence of sclerosis, LS mostly presents itself as a psoriasiform lichenoid dermatitis that may be difficult to distinguish from other diseases. Objective We sought to assess histopathologic findings that allow recognition of LS in the absence of sclerosis. Methods We studied 28 criteria in 100 biopsy specimens of LS from genital or perianal skin, including 55 cases with marked sclerosis, 16 cases with mild sclerosis confined to foci of the papillary dermis and 29 cases without sclerosis. Fifteen cases each of the early plaque stage of mycosis fungoides, lichen planus and lichen simplex chronicus were studied for comparison. Results Some histopathologic hallmarks of LS were seen chiefly in sclerotic lesions and, therefore, did not contribute to the diagnosis of difficult cases, such as dissolution of elastic fibers. Others were seen rarely in non‐sclerotic lesions but might be helpful in individual cases, including follicular hyperkeratosis and thickening of the basement membrane. Findings that were more common and may be utilized as clues to the histopathologic diagnosis of non‐sclerotic LS include tiny foci of homogenized tissue in dermal papillae, marked fibrosis with thickening of the papillary dermis, marked thickening of individual collagen fibers, lymphocytes aligned in rows between those fibers, necrotic keratinocytes, often with preserved pyknotic nuclei, in all reaches of the epidermis, including the cornified layer, clustering of necrotic keratinocytes above elongated dermal papillae and vertical columns of parakeratosis with distinct dyskeratotic parakeratotic cells. Conclusion In the absence of sclerosis, histopathologic diagnosis of LS depends on findings that are less distinctive. Nonetheless, a constellation of those findings allows a specific diagnosis to be made.